SOSIALISASI “ISI PIRINGKU” SEBAGAI PENCEGAHAN STUNTING DI RAUDLATUL ATHFAL TANWIRUT TULAB PAYUNG MAKMUR LAMPUNG TENGAH - Ayu, Riska Nur Suci; Surahman, Novriansyah (LPPM Institut Pendidikan Nusantara Global, 2023)
Stunting is a chronic condition resulting from nutritional deficiencies that can lead to toddlers having a stature/height shorter than their age would typically indicate. The prevention of stunting can be achieved through the provision of education and the implementation of nutritional fulfillment for children based on the